Given: nth term of an A.P (an) = pn + q
To find: Common Difference (d)
Proof: We know that,
an = a + (n – 1)d
⇒ pn + q = a + (n – 1)d [given]
⇒ pn + q – a = (n – 1)d
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Glimpses of India39 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation